Exploring Structural Changes, Manufacturing, Joining, and Repair of Intermetallic γ‐TiAl‐Based Alloys: Recent Progress Enabled by In Situ Synchrotron X‐Ray Techniques. Issue 11 (27th January 2021) - Spoerk-Erdely, Petra; Staron, Peter; Liu, Jie; Kashaev, Nikolai; Stark, Andreas; Hauschildt, Katja; Maawad, Emad; Mayer, Svea; Clemens, Helmut
Abstract : Intermetallic γ‐TiAl‐based alloys are a promising class of materials for lightweight high‐temperature applications. Following intensive research and development activities, they have recently entered service in the automotive and aircraft engine industries. In the course of the past decades, the development of these complex multiphase alloys has benefited considerably from the application of (in situ) X‐ray scattering and diffraction techniques. Herein, a practical introduction and overview of recent progress in this field of research are provided. In particular, four case studies taken from various stages in the alloy development (i.e., fundamental research—manufacturing, joining, and repair—and application) illustrate current prospects at modern synchrotron radiation sources, including detailed information on available setups for in situ high‐energy X‐ray diffraction and small‐angle X‐ray scattering experiments and a discussion of potential limitations in the use of these techniques. Abstract : Intermetallic γ‐TiAl‐based alloys are promising structural materials for lightweight high‐temperature applications. During the past decades, their development has benefited greatly from the application of (in situ) X‐ray diffraction and scattering techniques based on high‐energy synchrotron X‐rays. This review, which includes four detailed case studies, seeks to provide a practical introduction and overview of recent progress in this field.